Periodontal bacteria DNA findings in human cardiac tissue - Is there a link of periodontitis to heart valve disease?. (15th January 2018) - Ziebolz, D.; Jahn, C.; Pegel, J.; Semper-Pinnecke, E.; Mausberg, R.F.; Waldmann-Beushausen, R.; Schöndube, F.A.; Danner, B.C.
Abstract: Background: The aim of the study was to detect periodontal pathogens DNA in atrial and myocardial tissue, and to investigate periodontal status and their connection to cardiac tissue inflammation. Methods: In 30 patients, biopsy samples were taken from the atrium (A) and the ventricle myocardium (M) during aortic valve surgery. The dental examination included the dental and periodontal status (PS) and a collection of a microbiological sample. The detection of 11 periodontal pathogens DNA in oral and heart samples was carried out using PCR. The heart samples were prepared for detecting the LPS-binding protein (LBP), and for inflammation scoring on immunohistochemistry (IHC), comprising macrophages (CD68), LPS-binding protein receptor (CD14), and LBP (big42). Results: 28 (93%) patients showed moderate to severe periodontitis. The periodontal pathogens in the oral samples of all patients revealed a similar distribution (3–93%). To a lesser extent and with a different distribution, these bacteria DNA were also detected in atrium and myocardium (3–27%). The LBP was detected in higher amount in atrium (0.22 ± 0.16) versus myocardium (0.13 ± 0.13, p = 0.001). IHC showed a higher inflammation score in atrial than myocardial tissue as well as for CD14, CD68 and for LBP. Additional, periodontal findings showed a significant correlation to CD14 and CD68. Conclusion: The results provide evidence of the occurrence of oral bacteria DNA at the cardiac tissue, with a different impact on atrial and myocardial tissue inflammation. Influence of periodontal findings was identified, but their relevance is not yet distinct. Therefore further clinical investigations with long term implication are warranted.